Quantitative evaluation of Mycobacterium abscessus clinical isolate virulence using a silkworm infection model. - Yasuhiko Matsumoto; Hanako Fukano; Naoki Hasegawa; Yoshihiko Hoshino; Takashi Sugita (PLoS ONE, 2022)
Mycobacterium abscessus causes chronic skin infections, lung diseases, and systemic or disseminated infections. Here we investigated whether the virulence of M. abscessus clinical isolates could be evaluated by calculating the median lethal dose (LD50) in a silkworm infection model. M. abscessus subsp. abscessus cells were injected into the silkworm hemolymph. When reared at 37˚C, the silkworms died within 2 days post-infection with M. abscessus subsp. abscessus. Viable cell numbers of M. abscessus increased in the hemolymph of silkworms injected with M. abscessus. Silkworms were not killed by injections with heat-killed M. abscessus cells. The administration of clarithromycin, an antibacterial drug used to treat the infection in humans, prolonged the survival time of silkworms injected with M. abscessus. The LD50 values of 7 clinical isolates in the silkworm infection model were differed by up to 9-fold. The Mb-17 isolate, which was identified as a virulent strain in the silkworm infection model, induced more detachment of human THP-1-derived macrophages during infection than the Mb-10 isolate. These findings suggest that the silkworm M. abscessus infection model can be used to quantitatively evaluate the virulence of M. abscessus clinical isolates in a short time period.